Inside the Padded Sphere: The phenomenology and existential analysis of the schizoid personality (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
This paper offers an existential-phenomenological perspective on the schizoid personality, its struggles, coping capacities, and creative strategies. The writings of Kierkegaard, particularly in terms of his exploration of the concept of 'shut-upness,' or 'inclosing reserve,' and its relationship to despair can be decisively instructive in facilitating and promoting the therapeutic process.
Keywords: Abstraction; Buber; despair; disembodiment; Kierkegaard; Laing; loneliness; phenomenology; shut-upness; schizoid